Do Ciphers Have Politics?: Discourses Of The Digital Rights Movement In The Crypto Wars 2.0 - West, Sarah Myers (AoIR Selected Papers of Internet Research, 2017)
Encryption is a technical process that has become imbued with tremendous social and political value. It is a critical part of the infrastructure of the Internet, making it possible to safely and securely transmit messages across the network. Like other forms of infrastructure, encryption could be seen as boring and mundane, “singularly unexciting” (Star, 1999). Despite this, encryption technologies have attracted a tremendous amount of attention in recent years due to debates over whether and under what conditions digital information should be encrypted. These debates center on a contestation over two incompatible readings of the sociopolitical value of encryption: on the one hand, historical associations of encryption with the state, and on the other, more contemporary interpretations of encryption as a form of protection against mass surveillance. This paper seeks to tease out these divergent associations of encryption by parsing the encryption debate, a policy battle that has been termed the Crypto Wars 2.0 – a term intended to evoke a similar policy debate in the 1990s. I attend particularly to the development of a discourse associating encryption with human rights between the 90s and present day, exploring its politics through participant observation at digital rights conferences and interviews with privacy advocates, policy officials engaged in the debate, and technologists currently working on encryption projects. In so doing, I aim to describe the development of a new political imaginary for encryption in the networked age, one which seeks to redistribute power away from institutions and back to individuals.